Should Robotic Surgery Simulation Be Introduced in the Core Surgical Training Curriculum? - Bhakhri, Kunal; Harrison-Phipps, K.; Harling, Leanne; Routledge, T. (Frontiers in Surgery, 2021)
Introduction The focus of this research is to qualitatively analyse the literature and address the knowledge gap between robotic surgery simulation (RoSS) and core surgical training curriculum. It will compare the effectiveness and the benefits of using robotic simulators in training as compared to the current standard training methods. Materials and Methods A qualitative research of literature was carried out with the use of critical analysis formatting to expand the search. The inclusion criteria entailed selecting academic resources that focused on Robotic Surgery Simulation (RoSS) and core surgical curriculum. The Online databases used in the search took into account information retrieval from stakeholders. Evidence Synthesis In this article, we compiled and scrutinised the available relevant literature comparing performance assessments, surgical skills transfer and assessment tools between robotic surgery simulation (RoSS) and current training platforms in open and minimal access surgery. Data that has been published underpins the authenticity of robotic Surgery Simulation (RoSS), based on a combination of observational evaluation and simulation scores. Conclusion The introduction of robotic surgery simulation (RoSS) has the potential to bring major improvements in the surgical training curriculum . RoSS platforms are more robust in terms of ensuring rapid surgical skills transfer/ acquisition, assessment is standardised, unbiased and the training covers non technical skills aspects.